Suprapubic Transvesical Repair of Vesicovaginal Fistula Using a Homemade Laparoscopic Single-Port Device: Experience of 42 Patients - Fan, Xinxiang; Ma, Xiaoming; Lai, Yiming; Li, Zean; Huang, Jian; Huang, Hai (Frontiers in Surgery, 2021)
Aim: Vesicovaginal fistula (VVF) is the most common urogenital acquired fistula, and has remained a scourge and of public health importance. VVF can be repaired by transvaginal approach, transabdominal approach or transvesical approach, but the optimal management is still debated. Methods: To demonstrate a suprapubic transvesical approach to repair VVFs using a homemade laparoscopic single-port device. A retrospective review of the medical records of 42 consecutive patients who underwent fistula repair for VVF at our center from January 2012 to March 2018 was performed. VVFs were repaired by a suprapubic transvesical approach using a homemade laparoscopic single-port device. Clinical data, perioperative data and outcomes were collected. The primary outcome was VVF successful closure rate, and secondary outcome was perioperative complications. Results: The mean age of the patients was 44.6 (27–58) yr. The mean follow-up time was 65.6 (32–118) mo. The VVFs were successfully closed in 37 (88.1%) patients after the first surgery, and failure was observed in five patients. Initial failures of all the five patients were cured after a second repair. No major complication occurred as defined by Clavien-Dindo class 2 or greater. Conclusions: Suprapubic transvesical approach to repair VVFs using a homemade laparoscopic single-port device is a simple, effective, and feasible approach offering ideal results without major complications.